Beyond the Bubble: Three empirical reasons for re-conceptualizing online visibility - Madsen, Anders Koed (MedieKultur: Journal of media and communication research, 2016)
Google is a powerful player in deciding how the world is represented to information-seeking citizens in a digitized knowledge-society. Eli Pariser has been influential in arguing that the company’s algorithm leave its users trapped in a biased ‘filter bubble’ where information about the world is tailored to their preferences by algorithms. This paper proposes a move away from the metaphor of the ‘bubble’ when trying to understand how ‘real world representations’ are shaped by dynamics of online visibility. Instead of a mono-causal focus on the algorithm, it suggests focusing on the distributed set of selection mechanisms that enable web-users to navigate a world of ‘big data’. The paper suggests a conceptual move from ‘bubbles’ to ‘visions’ when understanding online visibility. It motivates this suggestion through three empirical analyses of the selection mechanisms involved in making the issue of synthetic biology visible to British Google’s users from February 2011 – February 2012. The paper uses the findings of these analyses as a basis from which to suggest theoretical, empirical and practical implications for future studies on the impact of the digital on ‘real world representation’.